Pengaruh Karakter Wirausaha Terhadap Life Skill siswa Sekolah Menengah Kejuruan Nusantara Indah Sintang Tahun 2020/2021 - Finika Nuela; Anna Marganingsih; Yunita Astikawati (JURKAMI : Jurnal Pendidikan Ekonomi, 2021)
The purpose of this research is quantitative research. The population in this study were 72 students of class XI and XII majoring TKJ SMK Nusantara Indah Sintang. The sampling technique in this study using saturated sampling with the number of respondents as many as 72 students. Data analysis used validity and reliability testing, descriptive analysis test, contribution test, and classical assumption test, correlation test, determination test and hypothesis testing. The results showed that the entrepreneurial character had an effect on the life skills of the students of SMK Nusantara Indah Sintang, with the results of the t test, it was obtained that the t-count value was 1.981 which was greater (>) t-table 1.660 and the result of the Sig. 0.002 <0.05. The closeness of the relationship between the X and Y variables is 0.600. Based on the results of data analysis, it means that the level of closeness of the relationship between the variables of business character and life skills is moderate or sufficient. The coefficient of determination is 0.360, that 36% of the life skills of the students of SMK Nusantara Indah Sintang are influenced by entrepreneurial characters and the remaining 64% is influenced by other variables